PRODUCTION AND OPTIMIZATION OF L-GLUTAMINASE ENZYME FROM Hypocrea jecorina PURE CULTURE - Bulbul, Dilara; Karakus, Emine (TAYLOR & FRANCIS INC, 2013)
L-Glutaminase (L-glutamine amidohydrolase, EC 3.5.1.2) is the important enzyme that catalyzes the deamination of L-glutamine to L-glutamic acid and ammonium ions. Recently, L-glutaminase has received much attention with respect to its therapeutic and industrial applications. It acts as a potent antileukemic agent and shows flavor-enhancing capacity in the production of fermented foods. Glutaminase activity is widely distributed in plants, animal tissues, and microorganisms, including bacteria, yeasts, and fungi. This study presents microbial production of glutaminase enzyme from Hypocrea jecorina pure culture and determination of optimum conditions and calculation of kinetic parameters of the produced enzyme. The optimum values were determined by using sa Nesslerization reaction for our produced glutaminase enzyme. The optimum pH value was determined as 8.0 and optimum temperature as 50 degrees C for the glutaminase enzyme. The Km and Vmax values, the kinetic parameters, of enzyme produced from Hypocrea jecorina, pure culture were determined as 0.491mM for Km and 13.86U/L for Vmax by plotted LineweaverBurk graphing, respectively. The glutaminase enzyme from H. jecorina microorganism has very high thermal and storage stability.
Keywords: enzyme production; glutaminase; Hypocrea jecorina; L-glutamine; Nessler reagent; SALT-TOLERANT; ASPARAGINASE; GLUTAMATE; Biochemistry & Molecular Biology; Biotechnology & Applied Microbiology